ANALISA KERUSAKAN PADA PLAT PENGARAH (SHOVEL) MESIN PENGGILING NATURAL CLAY - Siagian, Tony (MEKANIK: Jurnal Ilmiah Teknik Mesin, 2016)
Shovel is one of the important parts in the clay grinding machine component, where this component serves to direct the material that is milled in the mill between the roller and roller bearings. With the high rate of replacement of this shovel material due to wear will have an impact on the decline in engine productivity due to lost working hours. Shovel material is made from Hardox 400 material where the value of BHN material hardness: 370 - 430, the value of material hardness is very influential in determining the age of the shovel, but still calculated from the side of the collision load that occurs during grinding. From the results of testing both macro testing and micro testing it is known that the value of material hardness (Hardness test) is not in accordance with the specifications of the material which is around 37% below the specification value. And from the SEM test results it can also be observed that there has been a significant change in the grain structure of the matrial surface and scouring on the shovel samples that have been used.